PENGARUH ASIMETRI INFORMASI, TINGKAT LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA DALAM LAPORAN TAHUNAN PERUSAHAAN INDEKS LQ-45 DI BURSA EFEK INDONESIA - Featy Octaviany (POLITEKNIK LP3I JAKARTA, 2013)
The purpose of this research is to test the asymmetry of information variable, levels of leverage, and the company size that are expected to affect earnings management in annual reporting companies included in the LQ-45 firms in Indonesia Stock Exchange. The population data in this research is consists of 78 companies, while the sample data that is used is 26 companies that includes LQ-45 index in the period February 2008 to January 2011 using annual reports from each company for the fiscal year 2008 to 2010. Data were analyzed by using the classical assumption test and multiple linear regression analysis. The results of this study indicate that the asymmetry of information variable and the company size variable had no significant effect on earning management in corporate annual reports. This is proved by the Significant Value of the asymmetry of information variable is 0,129 and the correlation coefficient is -0,183 that shows that the asymmetry of information variable has a weak relation with the earnings management. While the company size variable had a Significant Value about 0,069, and the correlation coefficient is -0,138 that shows that the company size variable has a weak relation with the earnings management. The two variables had a greater value than the significant level. While levels of leverage variabel indicates that this variabel had significant effect on earnings management in corporate annual reports. This is proved by the Significant Value of levels of leverage variable is 0,000 which is below than the significant level and the correlation coefficient is 0,509 that shows that levels of leverage variable has enough strong relation with the earnings management. It can be concluded that the companies included in the LQ-45 never had done earning management in their company although there is the asymmetry of information, and also had no significant effect to the size of the company that included in the LQ-45 so that the two factors used in this study does not significantly affect earning management in annual reporting. Meanwhile, level of leverage can affect earning management in annual reporting because sometimes a company that has a high levels of leverage usually do earning management by increasing or decreasing the profit of the company compare to the company that has a low levels Of leverage. Keywords: information asymetry, level of leverage, size of the company, earning management